2012
DOI: 10.14430/arctic4168
|View full text |Cite
|
Sign up to set email alerts
|

Why Do They Need the Arctic? The First Partition of the Sea

Abstract: ABSTRACT. The political situation of the Arctic still remains unstable. In the past decade, a combination of the specific regulations of the Convention on the Law of the Sea and the phenomenon of Arctic ice-cover shrinkage have produced a significant increase in the political activity of some of the countries interested in the region. It is commonly thought that the roots of the Arctic conflict lie in the abundant mineral resources, particularly petroleum and natural gas, that lie under the Arctic seabed. By a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We adhere to this view as the Arctic Council has taken initiative to negotiate binding regional agreements in areas beyond national jurisdiction through past efforts such as the Agreement on Cooperation and Marine Oil Pollution Preparedness and Response and the Arctic Search and Rescue Agreement ( [41], pp. [4][5][6][7][8][9][10][11][12][13][14][15]. This precedent of binding treaties in waters outside of member EEZs demonstrates feasible legal basis for a regional treaty creating MPAs even beyond EEZs, though only binding for the 8 Arctic states and other parties that choose to accede to the treaty by way of future signature and ratification.…”
Section: Regional Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adhere to this view as the Arctic Council has taken initiative to negotiate binding regional agreements in areas beyond national jurisdiction through past efforts such as the Agreement on Cooperation and Marine Oil Pollution Preparedness and Response and the Arctic Search and Rescue Agreement ( [41], pp. [4][5][6][7][8][9][10][11][12][13][14][15]. This precedent of binding treaties in waters outside of member EEZs demonstrates feasible legal basis for a regional treaty creating MPAs even beyond EEZs, though only binding for the 8 Arctic states and other parties that choose to accede to the treaty by way of future signature and ratification.…”
Section: Regional Arrangementsmentioning
confidence: 99%
“…Global surface temperature data revealed that 2015 was the hottest year so far on record, since recordkeeping began in 1880 [8]. As a result of opening waters, economic activity and resource capture are accelerating in what some describe as possible "rush for the Arctic" [9], and others as the "scramble for the Arctic" [10]. Any "rush for the Arctic" will likely be slower than such a term implies, due to market prices and technological barriers, especially in the case of oil [8].…”
Section: Introductionmentioning
confidence: 99%